Transceive phase mapping using the PLANET method and its application for conductivity mapping in the brain. Issue 2 (4th September 2019) - Gavazzi, Soraya; Shcherbakova, Yulia; Bartels, Lambertus W.; Stalpers, Lukas J. A.; Lagendijk, Jan J. W.; Crezee, Hans; van den Berg, Cornelis A. T.; van Lier, Astrid L. H. M. W.
Abstract : Purpose: To demonstrate feasibility of transceive phase mapping with the PLANET method and its application for conductivity reconstruction in the brain. Methods: Accuracy and precision of transceive phase ( ϕ ± ) estimation with PLANET, an ellipse fitting approach to phase‐cycled balanced steady state free precession (bSSFP) data, were assessed with simulations and measurements and compared to standard bSSFP. Measurements were conducted on a homogeneous phantom and in the brain of healthy volunteers at 3 tesla. Conductivity maps were reconstructed with Helmholtz‐based electrical properties tomography. In measurements, PLANET was also compared to a reference technique for transceive phase mapping, i.e., spin echo. Results: Accuracy and precision of ϕ ± estimated with PLANET depended on the chosen flip angle and TR. PLANET‐based ϕ ± was less sensitive to perturbations induced by off‐resonance effects and partial volume (e.g., white matter + myelin) than bSSFP‐based ϕ ± . For flip angle = 25° and TR = 4.6 ms, PLANET showed an accuracy comparable to that of reference spin echo but a higher precision than bSSFP and spin echo (factor of 2 and 3, respectively). The acquisition time for PLANET was 5 min; 2 min faster than spin echo and 8 times slower than bSSFP. However, PLANET simultaneously reconstructed T1, T2, B0 maps besides mapping ϕ ± . In the phantom, PLANET‐based conductivity matched the true value and had the smallest spread of the three methods. In vivo, PLANET‐based conductivity was similar to spin echo‐based conductivity. Conclusion: Provided that appropriate sequence parameters are used, PLANET delivers accurate and precise ϕ ± maps, which can be used to reconstruct brain tissue conductivity while simultaneously recovering T1, T2, and B0 maps.